PENGEMBANGAN STRATEGI PEMASARAN KOPI REMPAH DESA TISTA (REDESTA) DALAM MENINGKATKAN PENDAPATAN BADAN USAHA MILIK DESA (BUMDES) - Putu Feby Eka Kawi Tantra; Luh Putu Mahyuni (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Tista Tourism Village, Kerambitan District is an area that has an attraction for visiting tourists because it has many potential tourism areas. The problem that arises in Redesta Coffee is that there is no promotional media to market superior products in Tista Village. The purpose of this community service is to empower the potential in Redesta Coffee marketing  by making packaging designs, logos, and brochures for marketing media as well as branding videos  contains reviews related to tourism potential and superior products regarding Tista Tourism Village. Methods pime Frame community service activities using three stages, namely, the planning phase (problem identification, output identification and interview guide), implementation stage (application permission, observation, interview, documentation), follow-up stage (video branding, brochure). The results of these activities yaitu provides brochure design Coffee Redesta and video branding (marketing) as a marketing medium of Redesta coffee. It is hoped that this study report can be used as reference material in other places in the framework promote tourism and its superior products in Bali.